2017
DOI: 10.1038/srep43360
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and in vitro biological properties of piezoelectric bioceramics for bone regeneration

Abstract: The piezoelectric effect of biological piezoelectric materials promotes bone growth. However, the material should be subjected to stress before it can produce an electric charge that promotes bone repair and reconstruction conducive to fracture healing. A novel method for in vitro experimentation of biological piezoelectric materials with physiological load is presented. A dynamic loading device that can simulate the force of human motion and provide periodic load to piezoelectric materials when co-cultured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
105
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 53 publications
3
105
0
2
Order By: Relevance
“…The highest piezoelectric coefficients, which quantify the generation of charge per unit of mechanical load, are currently achieved by lead‐based piezoelectric ceramics; however, their high lead content renders them toxic (Shrout & Zhang, ). Among the lead‐free piezoelectric systems, barium titanate (BT)‐based materials are a promising class for bone replacement as indicated by cytotoxicity, cell viability, and proliferation studies (Ball, Mound, Nino, & Allen, ; Baxter, Bowen, Turner, & Dent, ; Park et al, ; Tang et al, ; Zhang, Chen, Zeng, Zhou, & Zhang, ). Particularly, the BT‐derivative (Ba,Ca)(Zr,Ti)O 3 (BCZT) is of interest because of exceptionally high piezoelectric values compared to other lead‐free piezoelectric materials available today (Liu & Ren, ).…”
Section: Introductionmentioning
confidence: 99%
“…The highest piezoelectric coefficients, which quantify the generation of charge per unit of mechanical load, are currently achieved by lead‐based piezoelectric ceramics; however, their high lead content renders them toxic (Shrout & Zhang, ). Among the lead‐free piezoelectric systems, barium titanate (BT)‐based materials are a promising class for bone replacement as indicated by cytotoxicity, cell viability, and proliferation studies (Ball, Mound, Nino, & Allen, ; Baxter, Bowen, Turner, & Dent, ; Park et al, ; Tang et al, ; Zhang, Chen, Zeng, Zhou, & Zhang, ). Particularly, the BT‐derivative (Ba,Ca)(Zr,Ti)O 3 (BCZT) is of interest because of exceptionally high piezoelectric values compared to other lead‐free piezoelectric materials available today (Liu & Ren, ).…”
Section: Introductionmentioning
confidence: 99%
“…Given this fact, piezoelectric polymers and bioceramics had been investigated as potential substrates to accelerate bone regeneration . For example, piezoelectric poly(vinylidene fluoride) (PVDF) and barium titanate (BaTiO 3 ) were found able to promote osteogenic differentiation of pluripotent stem cells . Zhang et al prepared a kind of PVDF/BaTiO 3 composite membrane to promote the regeneration of rat calvarial defect through sustainably maintained in vivo electric microenvironment .…”
Section: Introductionmentioning
confidence: 99%
“…21,22 For example, piezoelectric poly(vinylidene fluoride) (PVDF) and barium titanate (BaTiO 3 ) were found able to promote osteogenic differentiation of pluripotent stem cells. 23,24 Zhang et al prepared a kind of PVDF/BaTiO 3 composite membrane to promote the regeneration of rat calvarial defect through sustainably maintained in vivo electric microenvironment. 25 These observations spurred interests and successes in using external ES to enhance bone regeneration and healing.…”
Section: Introductionmentioning
confidence: 99%
“…PLLA offers adjustable physical and mechanical properties and exhibits piezoelectricity (electrical charges generated by a mechanical force and vice versa) at a level comparable with collagen, the natural bone polymer . Indeed, it is known that surface charges can be used to modify cell behavior, and piezoelectricity has been explored in tissue repair applications . We have ourselves shown that protein adsorption is favored in poled PLLA areas, poling at temperatures higher than the polymer glass transition (T g ) producing polarization stable for up to 10 days, thus allowing for protein adhesion and cell proliferation in tissue growth strategies .…”
Section: Introductionmentioning
confidence: 94%